Research progress on the association between TMAO and vascular calcification in patients with chronic kidney disease - Yuxin Zhang; Liangying Huang; Santao Ou (Renal Failure)
Vascular calcification (VC) is a common complication in patients with chronic kidney disease (CKD) and a major risk factor for increased cardiovascular mortality in patients with CKD. Its pathology and pathogenesis are complex and have not been fully elucidated. Trimethylamine N-oxide (TMAO) is an enteric-borne uremic toxin that has been found to play a role in the progression of VC. This article mainly reviews the metabolism of TMAO, the relationship between TMAO and VC in CKD patients, and possible treatments for TMAO, aiming to further explore the mechanism of VC occurrence in CKD patients and provide potential diagnostic and treatment strategies.